Childhood adversities and psychopathology among military veterans in the US: The mediating role of social networks. (June 2019) - McLafferty, M.; Ross, J.; Waterhouse-Bradley, B.; Armour, C.
Highlights: Childhood adversities are associated with elevated levels of mental health problems in veterans. Quality of social networks is a protective factor, but quantity is not. Individuals who experience childhood adversities are less likely to have good social networks. Abstract: Childhood adversities can impact negatively on psychological health across the lifespan. Many military veterans have a history of adverse childhood experiences, which when combined with deployment related traumas, can lead to high levels of psychopathology. Social networks can however be protective. The current study aimed to identify typologies of childhood adversity in U.S. military veterans ( n  = 3092) and explore relationships between the adversity typologies and PTSD, mood and anxiety disorders, utilising data from the National Epidemiological Survey on Alcohol and Related Conditions-III (NESARC-III). The mediating role of quality and quantity of social networks were examined. Latent class analysis identified four adversity classes; 1) baseline, 2) household dysfunction, 3) maltreatment, and 4) multi-adversity. Individuals in the adversity classes (2–4), especially those who experienced multi-adversity had higher rates of psychopathology. The quality of social networks played an important mediating role, while quantity of networks did not. Those who experienced adversity were less likely to have supportive social networks, therefore adversity had both a direct and indirect impact on psychopathology. The findings highlight the importance of developing and maintaining social networks following military life. Recommendations include interpersonal skills training and programmes which may help them engage back into the community and enhance relationships.